Plutonium Uptake by Plants (A Review) - Shupik, A. A.; Edomskaya, M. A.; Synzynys, B. I.; Shavrina, K. E. (Biology bulletin of the Russian Academy of Sciences, 2024)
Information on the accumulation of plutonium by plants is summarized. The factors influencing the process of plutonium migration in the “soil–plant” system are considered. A review is given of plutonium transfer factors by plants as quantitative indicators of migration. It is shown that the plutonium transfer factors by plants are quite variable and cover six orders of magnitude. It is noted that, for a territory subject to global fallout, the transfer factors of plutonium are significantly lower than for pollution. For this purpose, special publications of the IAEA and publications on the study of the accumulation of plutonium for background territories and territories subject to radioactive contamination were considered. Data on the influx of plutonium into various agricultural crops grown at the Semipalatinsk test site are given. Transfer factors of plutonium by agricultural crops are in the range n × 10 –5 to n × 10 –1 for the territory of the Semipalatinsk test site. Published data on the accumulation of plutonium by wild vegetation growing in the Chernobyl fallout territory are considered. Transfer factors of plutonium by herbaceous vegetation for the territory of Chernobyl fallout are at the level of n × 10 –2 . Information on the plutonium transfer factors by various plants organs is summarized and presented. In general, based on the analysis of published data, the plutonium transfer factors are in the range n × 10 –7 to n × 10 –1 .